Esquerda pós-moderna e emancipação social: uma resposta ao Fórum Social Mundial - Gonçalves, Mauricio Bernardino [UNESP] (2010)
After 2001, with the emerging of the World Social Forum (WSF), the social fights and altermundialists mobilizations of the precedent decade have reached a new level. With the motto another world is possible, the global questioning to the international hegemonic neoliberal social order has been strengthen and the return of the necessity of one alternative way to the sociability of capital came up after more than three decades. Trying to represent one way of emancipation radically different from the ones tried during the most part of the 20th century, specially those connected to the social movement of work, in general qualified as belonging to an old left, the WSF has realized a type of critique both in theory and practice, in resume, a global critique to the form in which the social emancipation was usually conceived. This critique embraces specially marxism and the centrality attributed to the fight of work. One of its most important intellectuals is Boaventura de Sousa Santos. Even knowing that many of his arguments are valid, most properly against stalinism than against marxism, the new proposal is unable to overcome the limits of the sociability of capital in crisis and, in fact, reveals that the critique is limited to the theorical and practical horizon of the same neoliberal age that made its birth possible